2008
DOI: 10.1038/nn2071
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic NMDA receptor activity boosts intrinsic antioxidant defenses

Abstract: Intrinsic antioxidant defenses are important for neuronal longevity. We found that in rat neurons, synaptic activity, acting via NMDA receptor (NMDAR) signaling, boosted antioxidant defenses by making changes to the thioredoxin-peroxiredoxin (Prx) system. Synaptic activity enhanced thioredoxin activity, facilitated the reduction of overoxidized Prxs and promoted resistance to oxidative stress. Resistance was mediated by coordinated transcriptional changes; synaptic NMDAR activity inactivated a previously unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
501
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(541 citation statements)
references
References 51 publications
(86 reference statements)
32
501
1
4
Order By: Relevance
“…This preparation allows rapid access of exogenous Aβ and applied drugs to neural tissue and also simultaneous recording of eNMDARs and sNMDARs with a single patch electrode. In hippocampal autaptic cultures, we found that picomolar naturally occurring Aβ-soluble oligomers, nanomolar oligomeric Aβ 1-42 (but not monomeric), or low-micromolar Aβ [25][26][27][28][29][30][31][32][33][34][35] (but not Aβ ) induced a tonic inward current within tens of seconds of application in ∼55% of neurons (Fig. 2 A-G; n = 90).…”
Section: Aβ Increases Extrasynaptic Glutamatergic Currents But Decreasesmentioning
confidence: 95%
“…This preparation allows rapid access of exogenous Aβ and applied drugs to neural tissue and also simultaneous recording of eNMDARs and sNMDARs with a single patch electrode. In hippocampal autaptic cultures, we found that picomolar naturally occurring Aβ-soluble oligomers, nanomolar oligomeric Aβ 1-42 (but not monomeric), or low-micromolar Aβ [25][26][27][28][29][30][31][32][33][34][35] (but not Aβ ) induced a tonic inward current within tens of seconds of application in ∼55% of neurons (Fig. 2 A-G; n = 90).…”
Section: Aβ Increases Extrasynaptic Glutamatergic Currents But Decreasesmentioning
confidence: 95%
“…On the other hand, activation of synaptic NMDAR is not coupled to hippocampal neuron damage (Hardingham et al, 2002), but rather promotes resistance to oxidative insults and prevents accumulation of reactive oxygen species in cortical neurons (Papadia et al, 2008) (Fig. 1).…”
Section: Role Of Glutamatementioning
confidence: 99%
“…In fact, different independent papers reported that, unlike other classical NMDAR antagonists (e.g., MK801, AP5), memantine preferentially blocks extrasynaptic over synaptic NMDAR currents in neurons Xia et al , 2010 ). The importance of maintaining normal synaptic NMDA signaling has been interestingly underlined by Papadia et al who showed that synaptic NMDA activity is necessary to boost intrinsic antioxidant defenses (Papadia et al , 2008 ).…”
Section: Targeting Extrasynaptic Nmdars To Lower a β Peptide: Interesmentioning
confidence: 99%